Heterogeneidade dos padrões espaciais e temporais de incidência e mortalidade por Covid-19 no estado do Ceará, de 2020 a 2022 - Amaral, Mariana Prado (2023)
In order to characterize the distribution patterns in time and space of incidence and mortality related to covid-19 in Ceará in the years 2020 to 2022, a descriptive cross-sectional study was carried out, followed by an ecological study of the temporal trend of covid-19 cases in health professionals and the general population, as well as an ecological study of temporal trend and spatio-temporal analysis based on cases and deaths from covid-19 in Ceará. Secondary data provided by the State Health Department was used. Positive cases and deaths in which COVID19 was mentioned as the underlying or associated cause of death were used. The SaTScan, Joinpoint Regression, and ArcMap programs were used for processing and analysis. A total of 1,066,639 positive cases were recorded, of which 35,155 (3.29%) were in healthcare workers, and 31,716 (15.26%) deaths had covid-19 as the cause of death. Four epidemic waves were identified. The second wave had the highest volume of cases (44.51%) and deaths (54.84%). There was a significant difference between the temporal trends in the first and second waves in professionals to the population (p<0.001), for the third and fourth waves there was no difference (p=1.000). The second wave in the general population showed a more intense and lasting increase in incidence (WPCpop: 27.36%; 95%CI: 14.8 to 41.3) compared to professionals (WPCpro: 2.46%; 95%CI: 1.4 to 3.5). In the temporal analysis of incidence and mortality, there was a significant increase (WPC=38%; 95%CI: 33.5 to 43.9) and (WPC=86%; 95%CI: 77.5 to 95.8), followed by falls of -6.8% (95%CI: -7.8 to -6.0) and -11.7% (95%CI= -12.5 to -11.1), respectively. There were two further significant increases in incidence between EW 43 of 2020 and EW 09 of 2021 (WPC:4.3% and WPC: 26.6%) and a significant decline until EW 39 of 2021 (WPC:-17.9; 95%CI:-19.5 to -16.7). Mortality, on the other hand, rose sharply from wave 3 to wave 11 of 2021 (WPC: 29.5%; 95%CI: 25.9 to 34.4), followed by significant falls until wave 43 of 2021 (WPC: -17.4%; 95%CI: -18.9 to -16.2). The third and fourth waves of cases and deaths followed the same pattern, an intense increase, followed by falls in incidence and mortality. The spatio-temporal distribution of the first wave of incidence and mortality began in the capital and metropolitan region, spreading to the east and west coasts and then inland. On the other hand, in the other three waves, the clusters occurred simultaneously throughout the state. The study showed that priority vaccination, combined with other control measures, was fundamental in reducing the peak of the second wave in health workers. The dispersal of the disease in Ceará took place along tourist routes, followed by the internalization of the disease along highways. Once established, the disease consolidated in the state and the other waves occurred simultaneously in all regions of the state.